Pengaruh Penjualan Angsuran terhadap Kinerja Keuangan Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia : (Studi Kasus PT Astra Internasional Tbk) - Nur Anita Chandra Putry; Suyanto Suyanto; Satria Bufala Fery Airlangga; Silvester Hendry Kambe; Ansyah Denniar; Ferlana Biansyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
Installment sales are a strategy used by manufacturing companies to increase consumer purchasing power and sales volume, especially for high-priced products. PT Astra International Tbk, a manufacturing company listed on the Indonesia Stock Exchange (IDX), implements a credit sales system, particularly in the automotive industry. This study aims to analyze the impact of installment sales on the financial performance of PT Astra International Tbk during the 2023–2024 period. The approach used is quantitative descriptive with secondary data obtained from the company’s financial statements. The results show that credit sales have a positive effect on the company’s financial performance, especially in increasing revenue and profitability. However, this method also has the potential to increase receivables risk, which can affect the company’s liquidity if not managed properly. Therefore, companies need to manage receivables risk effectively to maintain financial health and ensure sustainable growth. This study provides insights into the management of installment sales in the context of manufacturing companies.